Education on Chin Tuck Exercises on Neck Pain for Batik Workers across the City of Jambi - Wanti Hasmar; Putra Hadi (Asian Journal of Healthcare Analytics, 2022)
Neck pain is a common problem that two out of three people will experience during their lifetime, 10% of all people will experience neck pain within one month. Injury/disease process to neck structures will result in muscle spasm and loss of movement function. Community service activities were carried out in June 2022 by giving leaflets about neck pain and chin tuck exercises, carried out 8 times. This PKM aims to be used as a source of knowledge and chin tuck exercises can be practiced on batik workers in Seberang Jambi City. The results of the evaluation both through questions and answers and demonstrations of the chin tuck exercise are that all batik workers can do these exercises independently so that they can reduce neck pain, muscle tension and increase cervical functional activities in batik workers.